Ablative Techniques for Image-Guided Thermal Ablation - Krokidis, Miltiadis; Hatzidakis, Adam (Digestive Disease Interventions, 2019)
Percutaneous image-guided thermal ablation is an established form of treatment of small volume hepato-pancreatico-biliary (HPB) tumors with very satisfactory results over the last three decades. Purpose of this article is to offer a brief overview of the history of thermal ablation and the currently available technology that interventional radiologists have in their armamentarium to offer minimally invasive thermally for HPB cancer.
Keywords: neoplasms; therapeutics; radiofrequency ablation; ablation techniques